Material didáctico en el desarrollo de competencias matemáticas en niños y niñas de la Institución Educativa Inicial n° 657 distrito de Punchana, Iquitos 2022 - Ihuaraqui Perez, Liz (2023)
The present investigation entitled "Didactic material in the development of mathematical competences in boys and girls of the Initial Educational Institution N° 657 Punchana District, Iquitos 2022, had as a general research question: How does the didactic material influence the development of mathematical competences in boys and girls of the Initial Educational Institution N°657, Punchana District, Iquitos 2022?, with the general objective of knowing the level of influence of the didactic material in the development of mathematical competences in boys and girls of the Initial Educational Institution N°657, Punchana District, Iquitos 2022, since for many years it has been observed that many of the students do not have an understanding of the problem of mathematics, as well as the procedures that help to improve the presentation of the results in the development of competencies. mathematics, for this reason the present seeks to establish the level of influence of didactic materials in the development of competence mathematical sciences, establishing a type of descriptive research, oriented to a non-experimental design in a population of 190 boys and girls of the Initial Educational Institution N°657, using for this purpose observation sheets aimed at collecting information in situ of the events that contribute to the collection of good information. The results were presented in frequency tables as well as bar graphs that help a better and efficient presentation of these results, reaching the following results, that students significantly improve the development of mathematical skills by correctly using the didactic materials in the classroom. learning process of mathematics, as well as the competence that has the best development is the competence to solve quantity problems, reaching the following conclusions that the use of didactic materials allows strengthening the knowledge of mathematical strategies in problem-solving issues As well as in the knowledge construction process, it also recommends that it is important to continue strengthening this process of using didactic materials in an efficient way that contributes to significantly improve the academic performance of initial level students.